Staphylococcus aureus Esx Factors Control Human Dendritic Cell Functions Conditioning Th1/Th17 Response - Cruciani, Melania (Front Cell Infect Microbiol, 2017)
The opportunistic pathogen Staphylococcus aureus (S. aureus) is a major cause of nosocomial- and community-acquired infections. In addition, many antibiotic-resistant strains are emerging worldwide, thus, there is an urgent unmet need to pinpoint novel therapeutic and prophylactic strategies. In the present study, we characterized the impact of infection with the pandemic methicillin-resistant USA300 S. aureus strain on human primary dendritic cells (DC), key initiators and regulators of immune responses. In particular, among staphylococcal virulence factors, the function of EsxA and EsxB, two small acidic dimeric proteins secreted by the type VII-like secretion system Ess (ESAT-6-like secretion system), was investigated in human DC setting. A comparative analysis of bacterial entry, replication rate as well as DC maturation, apoptosis, signaling pathway activation and cytokine production was performed by using wild type (wt) USA300 and three isogenic mutants carrying the deletion of esxA (ΔesxA), esxB (ΔesxB), or both genes (ΔesxAB). The S. aureus mutant lacking only the EsxA protein (ΔesxA) stimulated a stronger pro-apoptotic phenotype in infected DC as compared to wt USA300, ΔesxAB, and ΔesxB strains. When the mutant carrying the esxB deletion (ΔesxB) was analyzed, a higher production of both regulatory and pro-inflammatory mediators was found in the infected DC with respect to those challenged with the wt counterpart and the other esx mutants. In accordance with these data, supernatant derived from ΔesxB-infected DC promoted a stronger release of both IFN-γ and IL-17 from CD4(+) T cells as compared with those conditioned with supernatants derived from wild type USA300-, ΔesxAB-, and ΔesxA-infected cultures. Although, the interaction of S. aureus with human DC is not yet fully understood, our data suggest that both cytokine production and apoptotic process are modulated by Esx factors, thus indicating a possible role of these proteins in the modulation of DC-mediated immunity to S. aureus.